Digitalization of Sharia Entrepreneurship - Yunus Mustaqim; Nurani Puspa Ningruma (Urecol Journal. Part B: Economics and Business, 2021)
Digital technology currently has many positive impacts on the economy through increased productivity, the creation of product innovations and wide opportunities in creating new business units. This study analyzes the digitization of Islamic entrepreneurship. This research method uses library research with qualitative descriptive data analysis. The results of this study show that Islamic digital entrepreneurship is the product sold, product promotion, alternative payment that is in accordance with the rules and does not violate religious prohibitions (usury, gharar, maysir and haram). Because businesses must be able to use digital technology to gain strength in the supply chain, in this case businesses need to use technology to be able to distribute their products to consumers with maximum time and service. The connection with Islamic entrepreneurship, of course, until the distribution or delivery stage to customers, it is necessary to provide clear alternatives to consumers so that consumers are free to choose.